Bālayōgīśvara sandarśanaṃ - Aśōkkumār (Hētuvādi : Pratulaku, Samata Granthālayaṃ, 1976)
Poem criticizing the religious activism of Mummiḍivaraṃ Bālayōgi, b. 1930, Hindu yogi and advising people not to believe in religious leaders and to develop rational attitude.